2009
DOI: 10.1111/j.1750-3639.2008.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Detergent‐Insoluble EAAC1/EAAT3 Aberrantly Accumulates in Hippocampal Neurons of Alzheimer's Disease Patients

Abstract: Disturbed glutamate homeostasis may contribute to the pathological processes involved in Alzheimer's disease (AD). Once glutamate is released from synapses or from other intracellular sources, it is rapidly cleared by glutamate transporters. EAAC1 (also called EAAT3 or SLC1A1) is the primary glutamate transporter in forebrain neurons. In addition to transporting glutamate, EAAC1 plays other roles in regulating GABA synthesis, reducing oxidative stress in neurons, and is important in supporting neuron viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 69 publications
0
24
0
3
Order By: Relevance
“…For example, altered brain levels or localization of EAAT3 were also reported in patients suffering from schizophrenia (Bauer et al., 2008) and Alzheimer’s disease (Duerson et al., 2009). Also, in mouse models of Huntington’s disease, both impaired SorCS2 function (Ma et al., 2017) and aberrant EAAT3 localization leading to increased oxidative stress (Li et al., 2010) were reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, altered brain levels or localization of EAAT3 were also reported in patients suffering from schizophrenia (Bauer et al., 2008) and Alzheimer’s disease (Duerson et al., 2009). Also, in mouse models of Huntington’s disease, both impaired SorCS2 function (Ma et al., 2017) and aberrant EAAT3 localization leading to increased oxidative stress (Li et al., 2010) were reported.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were supported by additional studies indicating that knockdown of EAAT3 resulted in both epilepsy and limbic hyperexcitability (Sepkuty et al, 2002; Mathews and Diamond, 2003). Furthermore, studies have demonstrated the accumulation of detergent-insoluble EAAT3 in the hippocampus of patients with Alzheimer’s disease (Duerson et al, 2009), a neurodegenerative disorder that has a marked decrease in AMPAR levels during its early onset and progression (Chang et al, 2006; Hsieh et al, 2006). In addition, altered expression levels of the EAAT3 mRNA transcript and protein levels are observed in post-mortem brain tissue from individuals with schizophrenia (McCullumsmith and Meador-Woodruff, 2002; Huerta et al, 2006; Lang et al, 2007), following seizure activity (Ross et al, 2011) and epilepsy (Mathern et al, 1999; Simantov et al, 1999; Crino et al, 2002; Proper et al, 2002; Rakhade and Loeb, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this disparity are unclear but cannot represent methodological failure, as we are readily able to detect appropriate PCR products from brain tissues as shown in this study, and can similarly detect protein in the brain. 43 There may be several reasons for this disparity; thus, Jin et al 44 have previously described an alternate promoter for EAAC1, which yields a smaller EAAC1 protein. The involvement of multiple promoters in driving transcription of EAAC1 may occur in different tissue types and produce transcripts that display demonstrable heterogeneity at the 59 UTR.…”
Section: Discussionmentioning
confidence: 99%